2018
DOI: 10.1177/0003122418785371
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Education and the Advantage of a College Degree

Abstract: What is the worth of a college degree when higher education expands? The relative education hypothesis posits that when college degrees are rare, individuals with more education have less competition to enter highly-skilled occupations. When college degrees are more common, there may not be enough highly-skilled jobs to go around; some college-educated workers lose out to others and are pushed into less-skilled jobs. Using new measurements of occupation-level verbal, quantitative, and analytic skills, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 122 publications
3
71
0
Order By: Relevance
“…Many recent studies provide evidence that HE degrees are losing their value over time. For example, it has been found that HE jobs are rewarded less today in monetary terms (Bol, 2015;Figueiredo et al, 2013), that HE graduates' skills are being utilised less (Battu et al, 2000;Green & Zhu, 2010), and that HE graduates are increasingly crowding out secondary school leavers by entering non-graduate jobs (Boylan, 1993;Gesthuizen & Wolbers, 2010;Horowitz, 2018).…”
Section: Changes In the Value Of An He Degree In Recent Decadesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies provide evidence that HE degrees are losing their value over time. For example, it has been found that HE jobs are rewarded less today in monetary terms (Bol, 2015;Figueiredo et al, 2013), that HE graduates' skills are being utilised less (Battu et al, 2000;Green & Zhu, 2010), and that HE graduates are increasingly crowding out secondary school leavers by entering non-graduate jobs (Boylan, 1993;Gesthuizen & Wolbers, 2010;Horowitz, 2018).…”
Section: Changes In the Value Of An He Degree In Recent Decadesmentioning
confidence: 99%
“…Whereas HE was only accessible to privileged white males a century ago, it became an institution for the masses during the second half of the twentieth century (Batenburg & de Witte, 2001;Van der Ploeg, 1994;Wolbers, De Graaf, & Ultee, 2001). Most see the expansion of HE as a positive development that has improved human life, through private and socialeconomic returns, and by making work less physically demanding (Horowitz, 2018;Levy & Murnane, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among economists, skill-biased technological change has emerged as the favored theory to account for the surge in inequality from the 1970s (Autor, 2014). Meanwhile, sociological work stresses that these changes do not take place in a political vacuum (DiPrete and McManus, 1996;Horowitz, 2018;Kristal, 2013), and studies of the interplay between automation and organizational inequality highlight that there is no deterministic relationship between the two (Jürgens et al, 1993;Krzywdzinski, 2017). Instead, industry is a contested arena where politics shape not only how new production technologies are deployed, but to whose benefit (Busemeyer and Iversen, 2012;Gallie, 2017).…”
Section: Toward An Institutionally Informed Accountmentioning
confidence: 99%
“…The social capital available to children early in life has a strong effect on the likelihood of their eventually graduating college (Mayger, Hochbein, and Dever 2017), and Zheng (2017) found that selection effects account for a significant proportion of the effect of college education on health outcomes, but college education remains an independent predictor of those outcomes even after accounting for selection. Much of the research on returns to higher education is about the economic returns to education, focusing on it as a private good (for reviews, see Barrow and Malamud 2015;Hout 2012) and on relative effects of educational achievement (Horowitz 2018) and overmatch (Vaisey 2006). However, if college does increase civic engagement, and this effect is not due to selection, then scholars should also be focused on the public good that higher education can provide in the form of civic returns to education (AAAS, Commission on the Humanities and Social Sciences 2013; Allen 2016; Colby et al 2007).…”
Section: Original Articlementioning
confidence: 99%